U. S. - Moroccan Relations in the Context of the Anfa Conference - Karim Bejjit (Journal of Global Initiatives, 2019)
This essay seeks to shed new light on the intricate course of U.S.-Moroccan relations following the landing of American troops on the Atlantic coasts of Morocco. The Anfa Conference and Sultan Mohamed V’s dinner meeting with President Roosevelt marked an important stage in the process of Moroccan struggle for independence. Roosevelt’s personal interest in the Moroccan situation may have accentuated the inconsistencies in U.S. foreign policy in the 1940s regarding the French colonial empire and confronted its fundamental idealism with the exigencies of pragmatic politics. The vicissitudes of the war and America’s deep commitment to its French ally as well as its efforts to contain the spreading influence of communism across North Africa compelled the American administration to generally adopt an ambivalent position vis-à-vis Moroccan nationalist movement in its fierce pursuit for independence.